Adaptive behavior, sleep, and physical activity in adolescents with fetal alcohol spectrum disorder. (December 2022) - Hammond, Leah; Joly, Vannesa; Kapasi, Aamena; Kryska, Kathryn; Andrew, Gail; Oberlander, Tim F.; Pei, Jacqueline; Rasmussen, Carmen
Abstract: Background: Fetal alcohol spectrum disorder (FASD) is broadly associated with impairments to adaptive behavior and dysfunctional sleep. Associations between sleep, adaptive behavior, and physical activity are frequently drawn in discussions of typical development and other clinical conditions. Aims: In this study, we sought to characterize patterns of sleep, adaptive behavior, and physical activity in adolescents with FASD. We also investigated the associations between sleep, adaptive behavior, and physical activity within this population. Methods and procedures: Twenty-seven adolescents aged 11- to 17-years with a diagnosis of FASD and their caregivers participated in this study. All participants completed parent and youth questionnaires on adaptive behavior, sleep, and physical activity. Outcomes and results: Adolescents with FASD displayed significant impairments to all domains of adaptive behavior and considerable sleep disturbance. Worse sleep was associated with older age and sleep-related breathing disturbances were associated with poorer social adaptive behavior. Participation in physical activity, particularly organized sport, was strongly associated with better adaptive behavior. Conclusions and implications: Adolescents with FASD experience considerable challenges with regards to sleep and adaptive behavior. Physical activity, particularly organized sport, may provide opportunities for the improvement of adaptive behavior in this population. Highlights: Adolescents with FASD show broad adaptive behavior deficits. Adolescents with FASD displayed sleep difficulties. Most adolescents with FASD are not engaged in enough physical activity. Sleep problems were mostly unrelated to adaptive behavior impairments. Physical activity and organized sport were strongly related to adaptive behavior.